Turbulent Channel Flow: Direct Numerical Simulation-Data-Driven Modeling - Antonios Liakopoulos; Apostolos Palasis (Fluids, 2024)
Data obtained using direct numerical simulations (DNS) of pressure-driven turbulent channel flow are studied in the range 180 <semantics>≤</semantics><semantics>Reτ≤</semantics> 10,000. Reynolds number effects on the mean velocity profile (MVP) and second order statistics are analyzed with a view of finding logarithmic behavior in the overlap region or even further from the wall, well in the boundary layer’s outer region. The values of the von Kármán constant for the MVPs and the Townsend–Perry constants for the streamwise and spanwise fluctuation variances are determined for the Reynolds numbers considered. A data-driven model of the MVP, proposed and validated for zero pressure-gradient flow over a flat plate, is employed for pressure-driven channel flow by appropriately adjusting Coles’ strength of the wake function parameter, Π. There is excellent agreement between the analytic model predictions of MVP and the DNS-computed MVP as well as of the Reynolds shear stress profile. The skin friction coefficient Cf is calculated analytically. The agreement between the analytical model predictions and the DNS-based computed discrete values of Cf is excellent.